Contact Tools in Japanese Acupuncture: An Ethnography of Acupuncture Practitioners in Japan - Benjamin CW. Chant; Jeanne Madison; Paul Coop; Gudrun Dieberg (Medical Association of Pharmacopuncture Institute, 2017)
This study aimed to identify procedural elements of Japanese acupuncture, describe these elements in detail, and explain them in terms of the key thematic category of treatment principles. Between August 2012 and December 2016, ethnographic fieldwork was conducted in Japan. In total, 38 participants were recruited by chain referral and emergent sampling. Data was collected through participant observation, interviews, and by analyzing documents. A total of 22 participants agreed to clinical observation; 221 treatments were observed with 172 patients. Seventeen consented to formal interviews and 28 to informal interviews. Thematic analysis was used to critically evaluate data. One especially interesting theme was interpreted from the data: a variety of contact tools were applied in treatment and these were manipulated by adjusting elements of form, speed, repetition, and pressure. Tapping, holding, pressing/pushing, and stroking were the most important ways contact tools were used on patients. Contact tools are noninvasive, painless, can be applied in almost any environment, and may be easily accepted by patients worldwide. Contact tool theory and practice may be successfully integrated into acupuncture curricula outside of Japan, used to inform clinical trials, and contribute to an expanded repertoire of methods for practitioners to benefit individual patients in international contexts.